Analysis of Public Understanding of the Trade of Domestic Market Goods in Kota Pari Village Through the Digital Economy Towards Increasing Income - Meliana Indah Sari; Abdi Setiawan; Putri Aprilia; Rusmaini (International Forum of Researchers and Lecturers, 2022)
The purpose of this community research is to increase community understanding of the concept of trading goods in the domestic market through the digital economy so that there is an increase in income to the community in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency. The specific target of this community research is that the village community knows the concept of trading goods in the domestic market and the digital economy, for example in the traditional market closest to the settlement and the village area markets, and how the trade can expand its marketing network. The materials to be presented in this research are: Domestic market goods trading and the digital economy are related to increasing community income through community knowledge and skills related to the prices of agricultural products and home industry business products that will be traded throughout the village and urban areas. From this research, it is hoped that the community in Kota Pari Village, Pantai Cermin Subdistrict, Serdang Bedagai Regency, can know and understand the impact of domestic market trade in goods, such as the selling price of agricultural products, home industry business products, or other business products to increase the community's income.